2019
DOI: 10.18203/2320-1770.ijrcog20193529
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of indications of primary caesarean sections done at a tertiary care hospital

Abstract: Background: Caesarean section rates have globally risen above the levels that can be considered medically necessary. The aim of the study is to analyze the rate and indications of caesarean sections for primigravidae in the period 2016 to 2018 at a tertiary care hospital in Delhi.Methods: It is a retrospective observational study conducted in the Department of Obstetrics and Gynaecology at PGIMER and Dr RML Hospital, New Delhi. A total of 552 caesarean deliveries in primigravidae were studied.Results: The tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…This result correlates with the study done by Datta et al where the maximum primary caesarean were performed at 37-40 weeks of gestational age (74.14%). 5 In our study the number of emergency primary caesarean was 79.2% compared to 20.8% which was done as elective cases. This result correlates with the study done by Datta et al, Jain et al and Moni et al and other studies where the emergency caesarean sections were higher than elective caesarean.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…This result correlates with the study done by Datta et al where the maximum primary caesarean were performed at 37-40 weeks of gestational age (74.14%). 5 In our study the number of emergency primary caesarean was 79.2% compared to 20.8% which was done as elective cases. This result correlates with the study done by Datta et al, Jain et al and Moni et al and other studies where the emergency caesarean sections were higher than elective caesarean.…”
Section: Discussionmentioning
confidence: 55%
“…In a study done by Datta et al, it showed that the maximum number of cases (79.34%) had an age between 20-30 years which is very similar to the study done by Jain et al, Mande et al, by Rajbhandary et al, by Rao et al, Boyle et al as well as our study where the maximum age distribution was seen among 18-27 years of age (62.3%). 5,8,9,[11][12][13] This shows that most of the primigravida who underwent caesarean section were in the age group of 20-30 years in most studies. Our study had 16 elderly primigravida accounting to 4.2% of the study population.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations